Digital Skills of Blind College Students in the Educational Process during a Pandemic - Muh. Said; Wahyudi Hn; Siti Azizah; Darmawan Darmawan; Citra Rosalyn Anwar (Department of Special Education, 2022)
This article discusses the digital skills of blind students in the educational process during the pandemic. The COVID-19 pandemic forced most students to adapt to a new habit which is WFH (Working from Home). Meanwhile, blind students take longer to learn online which they barely knew about. During this pandemic, students are required to develop digital competencies even though they are studying from home. The purpose of this study is to identify and understand blind students' needs when they are studying from home during the pandemic. The research method used by the researcher in this research is descriptive qualitative, in which the data collection process is carried out online. The results of the analysis found that 7 aspects of blind students' ability in digital space were quite good. Those 7 aspects are basic knowledge of screen reader applications, basic knowledge of digital landscapes, basic knowledge of finding information, basic knowledge of tracing lecture references, basic knowledge of conversational applications and social media, basic knowledge of digital media skills, and ethics in using digital media. Although they are able in accessing or browsing in digital spaces, they are still lacking at some points regarding safety in digital spaces.